CircRNA: Functions, Applications and Prospects - Fei Xu; Qing Xiao; William W. Du; Sheng Wang; Burton B. Yang (Biomolecules)
Circular RNAs (circRNAs) represent a distinct class of covalently closed non-coding RNA molecules characterized by the absence of free 5′ and 3′ ends [...]